Critical review of off-axial nozzle and coaxial nozzle for powder metal deposition. (2021) - Kumar, S. Pratheesh; Elangovan, S.; Mohanraj, R.; Srihari, B.
Abstract: Direct Metal Deposition (DMD) is a technology in which metal powder is molten by a laser beam to generate a new layer with specific properties. In DMD, the metal powder is normally sprayed through the laser beam through an off-axial or coaxial nozzle. In the method, as per the manufacturer or the intended application, many possible variants, configurations, or geometries are familiar usage of both off-axial and coaxial nozzles. As it influences the mechanical properties and surface properties of the DMD-generated parts, it is important to select suitable nozzles for the process. Therefore, the objective of this paper is to research the design, the gas flow impact, and the influence of the parameters of the process and powder distribution of both off-axial and coaxial nozzles. The roughness on the surface and accuracy of the components provided by both nozzles are also discussed. The article gives detailed exposure to deposition rate, process efficiency, reliability, feed levels for powder, laser beam incident diameter, process speed, laser beam width, of both nozzles and mechanical properties, maintainability, and surface quality of the part produced in the DMD process. The study summarises the efficiency, flow rate, and usage of both off-axial and coaxial nozzles for the particular customised application.